Practicas agronómicas para reducir la velocidad de escurrimientos en laderas - Arreaga Morán, Reinaldo Clemente (2023)
Hillside runoff is one of the problems that has been occurring frequently, it starts when both the storage capacity of the surface and the interception power of the flora have been exhausted; from then on, a film of water flows over the surface and erodes the soil, since it flows towards the lower levels of the agricultural soil. The present research was paraphrased, simplified and subjected to a study in which the elementary principles and the importance of agronomic practices to reduce the velocity of runoff on slopes were analyzed. Based on the above, the following was determined: Agronomic practices make it possible to reduce the speed of runoff on slopes by means of a soil conservation system that complements and combines structural works, agronomic fertility measures and agroforestry; this system lies in its immediate application to be successful in the protection of slope soils. Living barriers consist of the implementation of perennial vegetation (trees or shrubs) built on slopes along the slope, their purpose is to reduce the flow of water on its surface while capturing and retaining the soil. The effect of strip tillage on erosion control is based on three principles: Different density of crops used; separation of sloping areas; and arrangement of plant contours. The effectiveness of the strips depends on the amount of sediment that can be stored, decreasing as it settles; it is only effective in the first rainfall and in those of low intensity, presenting no benefit when the rainfall is of high intensity. Contour seeding allows reducing the natural slope of the soil by planting on contour lines; this is a simple approach that requires a low initial investment and can effectively control water erosion.